Penataan Kawasan Komersil Di Pekanbaru Dengan Menerapkan Prinsip Urban Farming - Ahmad Ridho Darwis; Gun Faisal; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru city is predicted to be a service city and the largest economic center in the eastern part of Sumatra island. Various infrastructures begin to be built and developed without regard to environmental conditions that begin to deteriorate due to reduced green land and increased pollution. The high rate of development of new infrastructure in the middle of the city makes other buildings seem less interesting. For these reasons, it is necessary to restructure commercial area that starts to stop working as commercial area which is not only valuable, but also has a mission to maintain the ecology to balance the city environment. The area chosen for rearrangement is located at Jl. Tuanku Tambusai, Pekanbaru with an area of 4.5 Ha. Structuring commercial area uses design methods including finding issues, field data collection, literature studies and empirical studies. The final result is the creation of a commercial area by applying the principle of Urban Farming in order to realize an area that can support economic activities, keep the conditions of the city environment and be the balancer for the city environment. Keyword : Structuring, Commersial, Area, Urban Farming